VALUE ENGINEERING DALAM PEMBANGUNAN RUSUNAWA - Dita Pahang Putra, Nyoman; Mudjahidin, M (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
Value engineering is done to make an effort to organize systematically and applying a technique that identifies the product function that aims to meet the required function with the lowest price. Analytical Hierarchy Process method is used in the analysis phase of work plan to choices alternative that is more objective based on several variables. In the chart of the breakdown cost model, 7 items of work have the highest cost, based on the work items was found 2 items of work that have the potential to do great engineering work that is the value of the walls and ceiling. The application of the results of value engineering on the walls, recommended the bricks, concrete stiffeners, stucco 1:4, paint walls, ceramic that savings of Rp 92,578,941 or 13.6% of the total cost of initial construction. In the same way, for the ceiling work that is recommended to change the calsiboard hollow iron frame with GRC framework furing metal so that savings of Rp40, 499,036 or 17.3% and ceiling aluminum grill on the bathroom with the calsiboard furing metal frame so that savings of Rp20,226,477 or 40%. Total savings that occur: Rp7,036,167,661 ? Rp6,882,863,207 = Rp153,304,454 or 1.95% of total construction cost.